2007
DOI: 10.2337/dc07-0792
|View full text |Cite
|
Sign up to set email alerts
|

Nonalcoholic Fatty Liver Disease Is a Risk Factor for Type 2 Diabetes in Middle-Aged Japanese Men

Abstract: OBJECTIVE -To determine the association between nonalcoholic fatty liver disease and the risk for development of diabetes.RESEARCH DESIGN AND METHODS -We conducted an observational cohort study in male workers Ն40 years old in a Japanese company from 1997 to 2005. We excluded workers with alcohol intake Ն20 g/day and those with impaired glucose tolerance by a 75-g oral glucose tolerance test. The remaining 3,189 workers were classified into fatty liver (FL) and non-FL group based on the findings of abdominal u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

19
157
1
4

Year Published

2008
2008
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 221 publications
(183 citation statements)
references
References 43 publications
19
157
1
4
Order By: Relevance
“…There are now about 20 observational studies that have assessed the association between NAFLD and the risk of new-onset type 2 diabetes [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25].…”
Section: Epidemiological Evidence Linking Nafld To the Risk Of New-onmentioning
confidence: 99%
See 4 more Smart Citations
“…There are now about 20 observational studies that have assessed the association between NAFLD and the risk of new-onset type 2 diabetes [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25].…”
Section: Epidemiological Evidence Linking Nafld To the Risk Of New-onmentioning
confidence: 99%
“…The risk of diabetes among these published studies varied markedly from a 33% increase [14] to a 5.5 fold increase in risk [11]. This wide inter-study variation in risk might reflect differences in NAFLD severity, since the study by Park et al [15] showed that the 5-year incidence rate of type 2 diabetes increased progressively according to the ultrasonographic severity of NAFLD at baseline (normal: 7.0%, mild: 9.8%, moderate-to-severe: 17.8%) in a cohort of 25,232 South Korean nondiabetic middle-aged men.…”
Section: Epidemiological Evidence Linking Nafld To the Risk Of New-onmentioning
confidence: 99%
See 3 more Smart Citations